2008
DOI: 10.1158/0008-5472.can-07-5597
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor–β Regulates Mammary Carcinoma Cell Survival and Interaction with the Adjacent Microenvironment

Abstract: Transforming growth factor (TGF)-B signaling has been associated with early tumor suppression and late tumor progression; however, many of the mechanisms that mediate these processes are not known. Using Cre/LoxP technology, with the whey acidic protein promoter driving transgenic expression of Cre recombinase (WAP-Cre), we have now ablated the type II TGF-B receptor (TBRII) expression specifically within mouse mammary alveolar progenitors. Transgenic expression of the polyoma virus middle T antigen, under con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 49 publications
7
128
0
Order By: Relevance
“…GATA3 siRNA knockdown in T47D luminal breast cancer cells resulted in increased expression of a number of previously reported basal/myoepithelial markers including FOXC2, p-cadherin and CXCL1 (Rasbridge et al, 1993;Mani et al, 2007;Bierie et al, 2008) (Figure 5b (i)). Conversely, exogenous GATA3 expression in basal-like SUM149 cells resulted in downregulation of these same markers (Figure 5b (ii)).…”
Section: Brca1 and Gata3 Corepress Basal-like Breast Cancer Genes D Tmentioning
confidence: 64%
“…GATA3 siRNA knockdown in T47D luminal breast cancer cells resulted in increased expression of a number of previously reported basal/myoepithelial markers including FOXC2, p-cadherin and CXCL1 (Rasbridge et al, 1993;Mani et al, 2007;Bierie et al, 2008) (Figure 5b (i)). Conversely, exogenous GATA3 expression in basal-like SUM149 cells resulted in downregulation of these same markers (Figure 5b (ii)).…”
Section: Brca1 and Gata3 Corepress Basal-like Breast Cancer Genes D Tmentioning
confidence: 64%
“…Indeed, knockout of TGFBR2 in the fibroblasts of the tumor microenvironment resulted in upregulation of HGF, MSP, TGF-a, and other secreted factors that significantly en-98 npg hanced the adjacent epithelial cells to proliferate [5,96]. Surprisingly, these studies show that TGFBR2 knockout animals developed significantly more pulmonary metastases compared with control mice [35,[97][98][99]. In a recent report, researchers have shown that targeted deletion of TGFBR2 in mouse mammary epithelium initiates the recruitment of myeloid immune suppressor cells through the CXCL5 axis.…”
Section: Mouse Models Of Tgfβ and Metastasismentioning
confidence: 97%
“…The increase in intra-tumor neutrophil number observed following anti-TGFβ signaling therapy can be explained by the ability of TGFβ to inhibit endothelial adhesiveness of neutrophils and neutrophil transmigration in vivo [91]. Abrogation of TGFβ signaling in mammary carcinomas also led to increased infiltration of Gr-1 + CD11b + MDSCs into the invasive front of tumor tissues facilitating tumor cell invasion and metastasis through a process involving metalloproteinase activity [82,92]. Interestingly, MDSCs from TGFβ signaling deficient tumor-bearing hosts produced higher levels of VEGF, MMP-2, MMP-13 and MMP-14 than those isolated from normal mice [82].…”
Section: Tgfβmentioning
confidence: 99%